2002
DOI: 10.1080/080352502317371706
|View full text |Cite
|
Sign up to set email alerts
|

Size at birth and neonatal and postneonatal mortality

Abstract: Birthlength is strongly associated with both neonatal and postneonatal mortality; ponderal index is strongly associated with neonatal, but weakly with postneonatal mortality. The findings are consistent with previous hypotheses about a transient effect of ponderal index and a persistent effect of birthlength.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Infants born with “asymmetry” defined this way have higher rates of perinatal morbidity[ 40 ] and mortality. [ 41 ] In our study low weight, low length and low ponderal index were associated with CP, which corroborates previous findings. However, high ponderal index in our study was also associated with higher risk of CP.…”
Section: Discussionsupporting
confidence: 92%
“…Infants born with “asymmetry” defined this way have higher rates of perinatal morbidity[ 40 ] and mortality. [ 41 ] In our study low weight, low length and low ponderal index were associated with CP, which corroborates previous findings. However, high ponderal index in our study was also associated with higher risk of CP.…”
Section: Discussionsupporting
confidence: 92%
“…Kramer et al (1989) showed that disproportionality increased with increasing severity of growth restriction, suggesting the presence of a continuum of fetal growth restriction, rather than two distinct patterns. Regardless, several studies have shown associations between low ponderal index and risk of adverse perinatal outcomes (Cheung et al 2002; Fay et al 1991; Nieto et al 1998; Villar et al 1990). …”
Section: Discussionmentioning
confidence: 99%
“…Impaired fetal growth has been associated with neonatal morbidity and mortality ( Ashworth 1998 ; Cheung et al 2002 ). Additionally, the impact of fetal growth restriction has been shown to extend to chronic diseases of adulthood ( Barker et al 2002 ).…”
Section: Introductionmentioning
confidence: 99%